Breast Invasive micropapillary carcinoma: a rare neoplasm. In regards with a case - Martha Yudey Rodríguez Pino; Javier Martínez Navarro; Virgen Yazmín Martínez Navarro; Lisanka Fumero Roldán (Medisur)
Breast Invasive micro-papillary carcinoma is an aggressive and infrequent variant of breast cancer characterized by large lymphotropism and high frequency of lymph node metastases, regardless tumor size. It presents an unfavorable clinical prognosis, imaging studies do not show significant differences with the usual breast carcinomas and the immunohistochemical biomarkers expression is variable. For these reasons the case of a 52-year-old female patient is presented. She came with a hard and slightly mobile nodular mass in the upper left quadrant of the left breast. In the biopsy report it was classified as an invasive micropapillary carcinoma with lymphovascular infiltration and metastasis in eight of ten examined lymph nodes. Immunohistochemistry techniques were also performed.